2021
DOI: 10.1021/acs.jpclett.1c00188
|View full text |Cite
|
Sign up to set email alerts
|

Excitation-Dependent Triplet–Singlet Intensity from Organic Host–Guest Materials: Tunable Color, White-Light Emission, and Room-Temperature Phosphorescence

Abstract: A series of organic host–guest materials with multifunctional luminescence were constructed. Four isoquinoline derivatives were used as the guests, and benzophenone was used as the host. The doped system exhibited excellent dual emission with cyan fluorescence and orange-yellow room-temperature phosphorescence, and the dual emission could be combined into almost pure white-light emission. Importantly, the relative intensity of the fluorescence–phosphorescence could be adjusted by changing the excitation wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 44 publications
4
95
0
Order By: Relevance
“…S4), which is in line with our previous works. [40][41][42][43] Four other guest-host materials (MOPy/BPO, MAPy/BPO, DMOPy /BPO, and DMAPy/BPO, Fig. 1a) with the guest-host molar ratio of 1:1000 were further prepared, and the luminescence characteristics of the host-guest systems were systematically investigated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S4), which is in line with our previous works. [40][41][42][43] Four other guest-host materials (MOPy/BPO, MAPy/BPO, DMOPy /BPO, and DMAPy/BPO, Fig. 1a) with the guest-host molar ratio of 1:1000 were further prepared, and the luminescence characteristics of the host-guest systems were systematically investigated.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous works, we found that the host could assist the excitons of the guests in energy transfer. [41][42][43] So in this work, we first tested the excitation spectra (fluorescence emission/420 nm) of guest MAPy in common solvents (toluene, THF, and N,N-dimethylformamide/DMF) and host BPO (molten state and crystal state). As show in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, guest-host materials have gradually attracted more attention, [34][35][36][37][38][39][40][41] because the host molecules can inhibit the non-radiative transition of the guest energy in the guest-host system. [42][43][44][45][46][47] Additionally, several research results have shown that there is a synergy of energy between host and guest molecules, which can assist the guest molecules to transfer the excited state energy effectively. [39][40][41][42][43] Therefore, the guest-host system provides a new strategy for the construction of organic RTP materials with long-wavelength emissions and long lifetimes.…”
Section: Introductionmentioning
confidence: 99%